Mergenthaler Linotype Building: Chicago, Illinois (Oz, 1982)
The Mergenthaler Linotype Building, located between an expanding downtown core and the new intown "Dearborn Park" housing project, is part of a series of renovations occurring in the southern fringe of downtown Chicago. Known as Printers Row…